From Material Level to Structural Use of Mineral-Based Composites—An Overview - Katalin Orosz; Thomas Blanksvärd; Björn Täljsten; Gregor Fischer (Advances in Civil Engineering)
This paper surveys different material combinations and applications in the field of mineral-based strengthening of concrete structures. Focus is placed on mechanical behaviour on material and component levels in different cementitious composites; with the intention of systematically maping the applicable materials and material combinations for mineral-based strengthening. A comprehensive description of a particular strengthening system developed in Sweden and Denmark, denominated as Mineral-based Composites (MBCs), together with tests from composite material properties to structural elements is given. From tests and survey it can be concluded that the use of mineral-based strengthening system can be effectively used to increase the load bearing capacity of the strengthened structure. The paper concludes with suggestions on further development in the field of mineral-based strengthening.